Applicability of Adult Guidelines for Withholding or Terminating Resuscitation for Prehospital Traumatic Cardiopulmonary Arrest in Pediatrics - Bawazeer, Manal S.; Al Alawyat, Hanaa; Zamakhshary, Mohammed (European Journal of Pediatric Surgery, 2015)
Purpose The aim of this study is to assess the applicability to a pediatric population of adult guidelines for withholding or terminating traumatic cardiopulmonary resuscitation (CPR).Method Using a trauma registry database and patient data from May 2001 to February 2011, a retrospective cohort study was conducted for all trauma patients less than 18 years of age who arrived at the emergency department (ED) with no pulse at King Abdulaziz Medical City in Riyadh. The clinical criteria of the adult guidelines were applied to the study population; these criteria include an absence of pulse, apnea, unorganized electrocardiogram and fixed pupils (all observed at the scene). Then the outcomes of the studied patients were interpreted based on these guidelines; this analysis highlighted the relationship between the outcomes and the four clinical criteria of the adult guidelines.Results During the study period, 104 patients arrived at the ED with no pulse. CPR was initiated for only 44 of these patients. Unfortunately, every patient in this group died within 24 hours of ED arrival. Out of these 104 patients, 92 met the four clinical criteria of the adult guidelines, 11 met only three criteria, and one met only two criteria.Conclusion The clinical criteria of the previously published adult guidelines for terminating or withholding resuscitation correctly predicted 100% of the patient mortality when all criteria were met.
Keywords: prehospital traumatic cardiopulmonary arrest; guidelines; resuscitation; terminating; trauma registry